Idiopathic Granulomatous Mastitis Presenting as Bilateral Breast Abscesses. Issue 1 (21st December 2021) - Dierickx, Jesper; Dekeyzer, Sofie; Vanhoenacker, Filip
Teaching point: Idiopathic granulomatous mastitis is a rare disease that may present as breast abscesses and may mimic other inflammatory, infectious, or neoplastic disorders on imaging.